2007
DOI: 10.1038/sj.emboj.7601961
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection reveals that effectors couple dynamin's GTP-dependent conformational changes to the membrane

Abstract: The GTPase dynamin is a mechanochemical enzyme involved in membrane fission, but the molecular nature of its membrane interactions and their regulation by guanine nucleotides and protein effectors remain poorly characterized. Using site-directed fluorescence labeling and several independent fluorescence spectroscopic techniques, we have developed robust assays for the detection and real-time monitoring of dynamin-membrane and dynamin-dynamin interactions. We show that dynamin interacts preferentially with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
142
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 55 publications
10
142
0
Order By: Relevance
“…In wild-type mammalian cells, because actin burst occurs in the latter part of endocytosis, actin-induced stress could assist dynamin in scission. In addition, actin-induced in-plane stress in the neck domain could facilitate dynamin polymerization (60). This idea is supported by the recent work of Campelo and Kozlov (61), which predicts that high stress facilitates insertion of shallow proteins within the bilayer.…”
Section: Discussionsupporting
confidence: 66%
“…In wild-type mammalian cells, because actin burst occurs in the latter part of endocytosis, actin-induced stress could assist dynamin in scission. In addition, actin-induced in-plane stress in the neck domain could facilitate dynamin polymerization (60). This idea is supported by the recent work of Campelo and Kozlov (61), which predicts that high stress facilitates insertion of shallow proteins within the bilayer.…”
Section: Discussionsupporting
confidence: 66%
“…Through direct SH3-PRD interactions, these proteins can regulate dynamin self-assembly, GTPase activity and membrane binding (25)(26)(27)(28)(29)(30)(31). In order to uncouple the effect of curvature generation by their BAR domains from other effects on dynamin activity, we initially tested the ability of these proteins to synergize with truncated Dyn2 lacking its PRD (Dyn2⌬PRD).…”
Section: Full-length Endophilin and Amphiphysin But Not Snx9 Stimulatmentioning
confidence: 99%
“…In vitro studies have shown that these proteins can also regulate dynamin self-assembly, membrane binding, and GTPase activity (25)(26)(27)(28)(29)(30)(31). Thus, these proteins are good candidates for EAPs that could function, together with Dyn2, to enhance fission.…”
mentioning
confidence: 99%
“…Because the final tubules are circled by dynamin helices (8,20), it is thought that dynamin polymerization provides the energy needed to deform the liposome membranes into a highly curved tubular structure. Another explanation is that hydrophobic loops present in the PH domain of dynamin (18) could generate spontaneous curvature like the BAR domain structure (21), and that polymerization would just be required to stabilize the tubular shape. To discriminate between these hypotheses, forces and energies involved in polymerization have to be measured.…”
mentioning
confidence: 99%
“…Dynamin can also polymerize around preformed lipid nanorods of typically 10-to 15-nm radius containing PIP 2 (16) and around microtubules, onto which it was first purified (17). Binding of dynamin to liposomes has been shown to depend on liposome size (18), and theoretical calculations suggest that dynamin could be recruited by curvaturedriven long-range interactions between membrane-bound dimers of dynamin (19). Taken together, these observations may indicate that dynamin polymerizes preferentially along cylindrical structures with a radius close to its spontaneous radius of curvature.…”
mentioning
confidence: 99%